Design and comparative analysis of circuit theory model‐based slot‐loaded printed rectangular monopole antenna for UWB applications with notch band. (13th November 2022) - Yadav, Ashok; Singh, Pramod; Verma, Ramesh Kumar; Singh, Vinod Kumar
Summary: In this paper, a slotted printed rectangular monopole antenna (SPRMA) is proposed that covers the entire UWB (ultra‐wideband) except for WiMAX and WLAN (802.11/a‐n). In the first stage, a rectangular monopole antenna is designed, which covers the entire UWB frequency. Then, a T‐slot is inserted in the radiating patch to have the rejection of the band containing WiMAX and WLAN (802.11/a‐n). The notch characteristics of the proposed antenna are observed from 3.0 to 3.65 GHz and 4.5 to 6.65 GHz respectively. Measured peak gain of 3.28 dBi has been observed at 4.25 GHz frequency. To show the validation of antenna, mathematical analysis using circuit theory has been also given in the paper. The prototype has been also tested inside the anechoic chamber to give the validation in real‐time environment. Several other reported antenna structures have also the same notch band in UWB with different notching methods. The proposed structure's radiation properties are compared with other reported structures proving the compactness of the proposed structure. Abstract : In this paper, a slotted printed rectangular monopole antenna (SPRMA) is proposed that covers the entire UWB (ultra‐wideband) except for WiMAX and WLAN (802.11/a‐n). In the first stage, a rectangular monopole antenna is designed, which covers the entire UWB. Then a T‐slot is inserted in the radiating patch to have the rejection of the band containing WiMAX and WLAN (802.11/a‐n). The notch characteristics of the proposed antenna are observed from 3.0 to 3.65 GHz and 4.5 to 6.65 GHz, respectively. To show the validation of antenna, mathematical analysis using circuit theory has been also presented in the paper.